On Extension of Weibull Distribution with Bayesian Analysis using S-Plus Software - Bilal Ahmad Bhat (International Journal of Engineering and Management Research, 2018)
We introduce a new lifetime distribution which is an extension of Weibull distribution and yields a number of wellknown distributions as a special case. The Bayesian analysis using different priors is discussed using different priors with the help of S-Plus software as nowadays great attention has been given to Bayesian approach.